Motivating ESL students using vocabulary enrichment games / Emily Jothee Mathai and Suchithra Nair - Jothee Mathai, Emily; Suchithra, Nair (Universiti Teknologi MARA, Pulau Pinang & and Pusat Penerbitan Universiti (UPENA), 2005)
The maxim goes: you can fetch the horse to the water, but you cannot make him drink. In the ESL classroom, teachers can provide all the necessary circumstances and input, but learning will only materialize if learners are motivated to share the responsibility for the outcome. In other words, motivation is the prerequisite for learning. The fuller appreciation of the importance of motivation in language learning gives rise to a number of questions concerning the way in which content should be presented for learning. Numerous explorations in ESL methodology have suggested that motivating students through games sustain interests and encourage meaningful practice of language (Hansen, 1994). Within this context, this action research project explored the possibility of teaching vocabulary through games in two classes comprising learners enrolled in the Preparatory English Course (PEC) in Mara University of Technology with the primary aim of developing vocabulary knowledge in the direction of increasing reading proficiency. To evaluate the effectiveness of this approach, unstructured interviews and a questionnaire were used. As a means of measuring proficiency, learners' performance in a vocabulary test was analysed. Overall, the informal talks with the students revealed learners' increased awareness of new vocabulary without being aware they were learning and the conscious employment of vocabulary strategies. Correspondingly, students showed a significant improvement in motivation to carry out vocabulary related tasks. Implications of the findings for vocabulary development and reading skills enhancement in a language classroom were considered.